The lovemarks effect : winning in the consumer revolution. - Cassano, Silvano, ....-; Downer, Roger, ....-; Roberts, Kevin, 1949- (New York : powerHouse, 2006)
Kevin Roberts' book, The Lovemarks Effect: Winning in the Consumer Revolution, follows up from Lovemarks: the Future Beyond Brands and brings together the most engaging and insightful ideas and stories. This latest offering contains inspirational stories from Lovemarks Inspirational Owners and Consumers, metrics, practical advice, big ideas and examples of great work.
Keywords: Consumentengedrag; Marketing; Merken; Merkenbeleid